Model of intellectual evaluating the prospects of innovative project implementation (Путеводитель предпринимателя)
The need to build a system of innovative proposal selection is considered in the article, the model of intellectual evaluation of innovative project feasibility is described, algorithms of fuzzy pyramidal network building and their application for diagnostics of the internal and external environment ofindustrial enterprises are examined, and the procedure for obtaining an integrated evaluation of innovative project prospects is given.